ISWEO (Islamic work ethics online assessment and idea bank system) - Sa’ari, Haziah; Md Jali, Jafalizan; Idrus, Marlia; Nordin, Siti Khairiyah; Idris, Sufy Rabea Adawiya; Mohd Ramsi, Mohd Faizal; Abdul Aziz, Rafidah; Daud, Mohd Shamsul; Zainuddin, Intan Nurbaizura (Universiti Teknologi MARA, Kedah, 2017)
Islamic work ethics (IWE) is a concept of ethics that is based on Islamic teaching and principle which rely on faith. Meanwhile, organizational climate is the recurring patterns of behavior, attitudes and feelings that characterize life in the organization which later can foster affective employee commitment. Case studies have been conducted with an objective to explore the academic librarian’s perceptions towards IWE determinants being practiced in selected research universities. By using focus group instrument, 12 respondents have been selected to be involved in the study. The findings found that deeds and work intentions; justice, cooperation and trusteeship have close relationship with another construct in stimulating innovative behavior among academic librarians. From the analyzed findings, Islamic Work Ethics and Idea Bank Online Assessments for Organization @ ISWEO© - has been developed. ISWEO© is a web based system which assembles the identified of the major constructs in Islamic work practice. It is a solution for justly and efficient management to improve organizational climate and organizational culture in stimulate innovative behavior among academic librarians by measuring the transparency of parent organization in implementing work ethics according to Islamic teaching and practice. Specifically, the biggest beneficiary of ISWEO© system is to assess and evaluate the management in the research university libraries whereby the results will be contributed to the management improvement after analyzed. ISWEO© also provides a platform to collects ideas and relevant questions related to library management which later will be transformed into implementation for innovation agenda in the library’s landscape.